src/HOL/Semiring_Normalization.thy
 author haftmann Wed, 12 May 2010 15:27:15 +0200 changeset 36873 112e613e8d0b parent 36872 6520ba1256a6 child 37946 be3c0df7bb90 permissions -rw-r--r--
tuned proofs and fact and class names
```
(*  Title:      HOL/Semiring_Normalization.thy
Author:     Amine Chaieb, TU Muenchen
*)

header {* Semiring normalization *}

theory Semiring_Normalization
imports Numeral_Simprocs Nat_Transfer
uses
"Tools/semiring_normalizer.ML"
begin

text {* Prelude *}

class comm_semiring_1_cancel_crossproduct = comm_semiring_1_cancel +
assumes crossproduct_eq: "w * y + x * z = w * z + x * y \<longleftrightarrow> w = x \<or> y = z"
begin

lemma crossproduct_noteq:
"a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> a * c + b * d \<noteq> a * d + b * c"
by (simp add: crossproduct_eq)

"r \<noteq> 0 \<Longrightarrow> a = b \<and> c \<noteq> d \<Longrightarrow> a + r * c \<noteq> b + r * d"
proof (rule notI)
assume nz: "r\<noteq> 0" and cnd: "a = b \<and> c\<noteq>d"
and eq: "a + (r * c) = b + (r * d)"
have "(0 * d) + (r * c) = (0 * c) + (r * d)"
using add_imp_eq eq mult_zero_left by (simp add: cnd)
then show False using crossproduct_eq [of 0 d] nz cnd by simp
qed

"b = b + a \<longleftrightarrow> a = 0"
using add_imp_eq [of b a 0] by auto

end

sublocale idom < comm_semiring_1_cancel_crossproduct
proof
fix w x y z
show "w * y + x * z = w * z + x * y \<longleftrightarrow> w = x \<or> y = z"
proof
assume "w * y + x * z = w * z + x * y"
then have "w * y + x * z - w * z - x * y = 0" by (simp add: algebra_simps)
then have "w * (y - z) - x * (y - z) = 0" by (simp add: algebra_simps)
then have "(y - z) * (w - x) = 0" by (simp add: algebra_simps)
then have "y - z = 0 \<or> w - x = 0" by (rule divisors_zero)
then show "w = x \<or> y = z" by auto
qed

instance nat :: comm_semiring_1_cancel_crossproduct
proof
fix w x y z :: nat
have aux: "\<And>y z. y < z \<Longrightarrow> w * y + x * z = w * z + x * y \<Longrightarrow> w = x"
proof -
fix y z :: nat
assume "y < z" then have "\<exists>k. z = y + k \<and> k \<noteq> 0" by (intro exI [of _ "z - y"]) auto
then obtain k where "z = y + k" and "k \<noteq> 0" by blast
assume "w * y + x * z = w * z + x * y"
then have "(w * y + x * y) + x * k = (w * y + x * y) + w * k" by (simp add: `z = y + k` algebra_simps)
then have "x * k = w * k" by simp
then show "w = x" using `k \<noteq> 0` by simp
qed
show "w * y + x * z = w * z + x * y \<longleftrightarrow> w = x \<or> y = z"
by (auto simp add: neq_iff dest!: aux)
qed

text {* Semiring normalization proper *}

setup Semiring_Normalizer.setup

context comm_semiring_1
begin

lemma normalizing_semiring_ops:
shows "TERM (x + y)" and "TERM (x * y)" and "TERM (x ^ n)"
and "TERM 0" and "TERM 1" .

lemma normalizing_semiring_rules:
"(a * m) + (b * m) = (a + b) * m"
"(a * m) + m = (a + 1) * m"
"m + (a * m) = (a + 1) * m"
"m + m = (1 + 1) * m"
"0 + a = a"
"a + 0 = a"
"a * b = b * a"
"(a + b) * c = (a * c) + (b * c)"
"0 * a = 0"
"a * 0 = 0"
"1 * a = a"
"a * 1 = a"
"(lx * ly) * (rx * ry) = (lx * rx) * (ly * ry)"
"(lx * ly) * (rx * ry) = lx * (ly * (rx * ry))"
"(lx * ly) * (rx * ry) = rx * ((lx * ly) * ry)"
"(lx * ly) * rx = (lx * rx) * ly"
"(lx * ly) * rx = lx * (ly * rx)"
"lx * (rx * ry) = (lx * rx) * ry"
"lx * (rx * ry) = rx * (lx * ry)"
"(a + b) + (c + d) = (a + c) + (b + d)"
"(a + b) + c = a + (b + c)"
"a + (c + d) = c + (a + d)"
"(a + b) + c = (a + c) + b"
"a + c = c + a"
"a + (c + d) = (a + c) + d"
"(x ^ p) * (x ^ q) = x ^ (p + q)"
"x * (x ^ q) = x ^ (Suc q)"
"(x ^ q) * x = x ^ (Suc q)"
"x * x = x ^ 2"
"(x * y) ^ q = (x ^ q) * (y ^ q)"
"(x ^ p) ^ q = x ^ (p * q)"
"x ^ 0 = 1"
"x ^ 1 = x"
"x * (y + z) = (x * y) + (x * z)"
"x ^ (Suc q) = x * (x ^ q)"
"x ^ (2*n) = (x ^ n) * (x ^ n)"
"x ^ (Suc (2*n)) = x * ((x ^ n) * (x ^ n))"
by (simp_all add: algebra_simps power_add power2_eq_square power_mult_distrib power_mult)

lemmas normalizing_comm_semiring_1_axioms =
comm_semiring_1_axioms [normalizer
semiring ops: normalizing_semiring_ops
semiring rules: normalizing_semiring_rules]

declaration
{* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_semiring_1_axioms} *}

end

context comm_ring_1
begin

lemma normalizing_ring_ops: shows "TERM (x- y)" and "TERM (- x)" .

lemma normalizing_ring_rules:
"- x = (- 1) * x"
"x - y = x + (- y)"
by (simp_all add: diff_minus)

lemmas normalizing_comm_ring_1_axioms =
comm_ring_1_axioms [normalizer
semiring ops: normalizing_semiring_ops
semiring rules: normalizing_semiring_rules
ring ops: normalizing_ring_ops
ring rules: normalizing_ring_rules]

declaration
{* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_ring_1_axioms} *}

end

context comm_semiring_1_cancel_crossproduct
begin

declare
normalizing_comm_semiring_1_axioms [normalizer del]

lemmas
normalizing_comm_semiring_1_cancel_crossproduct_axioms =
comm_semiring_1_cancel_crossproduct_axioms [normalizer
semiring ops: normalizing_semiring_ops
semiring rules: normalizing_semiring_rules
idom rules: crossproduct_noteq add_scale_eq_noteq]

declaration
{* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_semiring_1_cancel_crossproduct_axioms} *}

end

context idom
begin

declare normalizing_comm_ring_1_axioms [normalizer del]

lemmas normalizing_idom_axioms = idom_axioms [normalizer
semiring ops: normalizing_semiring_ops
semiring rules: normalizing_semiring_rules
ring ops: normalizing_ring_ops
ring rules: normalizing_ring_rules
idom rules: crossproduct_noteq add_scale_eq_noteq
ideal rules: right_minus_eq add_0_iff]

declaration
{* Semiring_Normalizer.semiring_funs @{thm normalizing_idom_axioms} *}

end

context field
begin

lemma normalizing_field_ops:
shows "TERM (x / y)" and "TERM (inverse x)" .

lemmas normalizing_field_rules = divide_inverse inverse_eq_divide

lemmas normalizing_field_axioms =
field_axioms [normalizer
semiring ops: normalizing_semiring_ops
semiring rules: normalizing_semiring_rules
ring ops: normalizing_ring_ops
ring rules: normalizing_ring_rules
field ops: normalizing_field_ops
field rules: normalizing_field_rules
idom rules: crossproduct_noteq add_scale_eq_noteq
ideal rules: right_minus_eq add_0_iff]

declaration
{* Semiring_Normalizer.field_funs @{thm normalizing_field_axioms} *}

end

hide_fact (open) normalizing_comm_semiring_1_axioms
normalizing_comm_semiring_1_cancel_crossproduct_axioms normalizing_semiring_ops normalizing_semiring_rules

hide_fact (open) normalizing_comm_ring_1_axioms
normalizing_idom_axioms normalizing_ring_ops normalizing_ring_rules

hide_fact (open) normalizing_field_axioms normalizing_field_ops normalizing_field_rules

end
```